Developing New Media Literacy Among Secondary School Students In Malaysia: Case Studies Of Media Making On Environmental Issues - Prasad, Nunna Venkata (2011)
In the present new media world, it is essential for the students in Malaysia to develop a sense of media awareness and activism to facilitate social learning in relation to the surrounding world. In building a productive learning culture among the students, media literacy is a necessary intervention in developing critical understandings, creative abilities, and active participations. Developing new media literacy on environment among secondary school students in Malaysia is important as the world is becoming less green and the environment is declining. Students can contribute to this cause, by voicing their concerns, opinions and views by using their new media literacy skills on environment.